The strategic role of renewable energy in supporting net-zero emissions targets in industrial clusters: Pathways to achieving sustainability - Tamimi, Hafsah Afifah; Paramita, Chandra (Applied Environmental Science, 2025)
Background: Indonesia’s industrial sector has a high demand for electrical energy, contributing significantly to global energy consumption and greenhouse gas emissions. With 84.53% of national power generation relying on fossil fuels, concerns arise regarding energy security and environmental sustainability, particularly CO₂ emissions from coal-fired power plants. Method: This study examines CO₂ emission reduction through rooftop solar panel implementation in the Industrial Area. A combination of literature review and spatial analysis was used to assess emission reduction potential and formulate sustainable industrial strategies. Findings: The research estimates that rooftop solar panels can reduce greenhouse gas emissions by 0.15 Mt-CO₂e/year (literature study) and 0.04 Mt-CO₂e/year (spatial analysis). Spatial studies provide more precise estimations than literature-based approaches. Achieving these reductions requires increased funding, technology transfer, human resource investment, improved social acceptance, local actor empowerment, industrial coalitions, and policy updates. Conclusion: Transitioning to renewable energy in industrial areas can significantly reduce CO₂ emissions. However, comprehensive strategies integrating financial, technological, and policy support are essential for effective implementation. Novelty/Originality of this Study: This study uniquely compares literature-based and spatial analysis approaches to assess emission reduction potential. It also provides a strategic framework for sustainable industrial transformation, emphasizing the role of local and international collaboration in implementing renewable energy solutions.